Remittances, informal loans, and assets as risk-coping mechanisms: Evidence from agricultural households in rural Philippines - Marjorie C. Pajaron (University of the Philippines, School of Economics (UPSE), 2014)
This paper investigates whether agricultural households in rural Philippines insure their consumption and whether they use remittances, informal loans, or assets as ex post risk-coping mechanisms. Since these households have limited access to formal insurance and credit markets, any shocks to their volatile income can have substantial impacts. Using panel data and rainfall shocks as the instrumental variable for income shocks, this paper finds evidence that households depend on their networks of family and friends to partially insure their consumption. 2SLS and OLS estimates show that approximately 27 percent of consumption is insured. International remittances from migrant members replace about 11 percent of income decline while domestic transfers replace about 14 percent. Informal loans, however, decrease as rainfall shocks increase. Borrowers and lenders may be experiencing similar shocks, which would reduce the effectiveness of local risk-sharing arrangements.
Keywords: O12; Q12; D81; D12; F22; F24; 330; Risk-coping; Remittance; Informal loan; Consumption insurance; Rainfall shocks; Philippines